ANALISA KONTRUKSI JARINGAN TEGANGAN MENENGAH 20 KV TANPA KAWAT TANAH TERHADAP SAMBARAN INDUKSI PETIR Studi Kasus Di PT PLN ( Persero ) Area Semarang Rayon Boja Feeder BSB 4 GI BSB - Muhammad Nur Arif; Bambang Supradono; Agung Budi Santoso (PSTE UNIMUS, 2012)
A bolt of lightning strikes the induction is on the ground near a transmission line resulting in a phenomenon that caused of trensient electromagnetic fields from the lightning channel. This phenomenon is happening at lightning conductor wire. This event raised over voltage and resulting wave propagating on both sides of the wire in the strike lasts. In calculating the induction stroke used Shielded Factor (FP) is defined as the quotient ofthe induced voltage and induced voltage ground wire without a ground wire. If there is no ground wire, the neutral wire effect on induced voltage on the wire the same phase as the influence of the ground wire to the voltage induced in the phase wire. Since the neutral high wire above the ground is lower than the high-wire phase, greater than shielded factor of the channel with the ground wire. There are times when the neutral wire was installed over the wire so that the phase factor will be smaller shielded. Construction is crucial lightning disturbances. From this analysis concluded that the results obtained from data disruption due to lightning feeder PMT 4 GI BSB obtained 3 times a distraction while the calculation results showed interference by 4 times with 24.4 km length of the network there is no significant difference. Any differences due to changes in network construction are not communicated as elevation neutral wire that will affect shielded factor.